Research progress of exercise interventions on frailty in elderly patients with chronic diseases (老年慢性病患者衰弱运动干预研究进展) - ZHANG Jianhua (张建花); HUANG Shan (黄山); DENG Ying (邓颖) (Association of Integrative Nursing, 2024)
Frailty is a prevalent condition among elderly patients with chronic diseases, which seriously affects the life quality of patients and increases the vulnerability to adverse health outcomes. The exercise interventions are effective to prevent the onset of frailty and reverse frailty. This paper reviewed the studies of exercise interventions on frailty of elderly patients with chronic diseases, and provided reference for clinical intervention and practice of elderly patients with chronic diseases combined with frailty. (老年慢性病患者极易发生衰弱, 不仅严重影响患者生活质量, 还会增加其不良健康结局的易感性。运动干预不仅能预防衰弱, 甚至可以逆转其衰弱状态, 具有接受度高、不良反应少、效果明显等优势。本文综述老年慢性病患者衰弱运动干预的具体措施及效果评估, 以期为老年慢性病合并衰弱患者临床干预提供参考依据。)